PEMBUATAN ETANOL DARI UMBI TALAS (Colocasia esculenta [L] Schott) DENGAN PENAMBAHAN GELATIN SEBAGAI SUMBER NITROGEN Saccharomyces Cerevisiae - Abimanyu, Priem Reyhan; Kartika, Rudi; Sitorus, Saibun (Jurusan Kimia FMIPA UNMUL, 2019)
Ethanol have made from taro’s flour with an addition of gelatin as nutrition source for Saccharomyces cereviciae. Ethanol are made within process hydrolysis, fermentation, distillation and Gas Chromatography analysis. Starch hydrolysis process are enzymatic through liquification and saccharification process with an addition of alpha-amylase and gluco-amylase which conversed starch into glucose. Fermentation process are used time variation within 5, 6, 7 and 8 days and gelatin as nutrition source are used in concentration to 0,5 %, 1 % and 1,5 % (v/v). The highest ethanol concentration are obtained in addition of 1 % gelatin with 7 days of fermentation which are 41,648 %.